In situ thermoelastic stress analysis – an improved approach to airframe structural model validation. Issue 1 (2nd January 2019) - Rajic, Nik; McSwiggen, David; McDonald, Marcus; Whiteley, Don
ABSTRACT: The recent adaptation of uncooled infrared imaging technology to thermoelastic stress analysis (TSA) offers an opportunity to improve the validation basis for structural finite element modelling of complex airframe components. Uncertainties in modelling can lead to inaccurate airframe lifing predictions and premature test failures that delay and add cost to aircraft full-scale durability test programs. Traditional model validation practice relies on data drawn primarily from discrete strain gauge, structural deflection and load-cell measurements. Supplementing this data with full-field stress imagery is shown to lead to a significantly improved model validation capability. After reviewing the fundamentals of TSA and its application using uncooled infrared detectors this article describes an experimental study conducted on an F-35 full-scale durability test airframe. It is shown that small low-cost microbolometers installed on the airframe provide a rapid and unobtrusive means of obtaining high-fidelity full-field stress imagery of complex airframe components. Such data enables a direct and rapid assessment of model accuracy in areas of potentially life-limiting stress concentration where predictive accuracy needs to be most assured but has traditionally been difficult to verify using the established model validation approach. Issues of general relevance to the application of TSA to full-scale durability testing are also discussed.